Dynamics of earthworm species at different depths of orchard soil receiving organic or chemical fertilizer amendments - Mojtaba Yahyaabadi; Amir Hossein Hamidian; Sohrab Ashrafi (Eurasian Journal of Soil Science, 2018)
We investigated the dynamics of different earthworm species through the soil profile, which had received short-term amendments of either organic or inorganic fertilizer in an orchard during the spring of 2016. Earthworm populations were sampled at two consecutive depths of soil on 20 and 60 days after addition of fertilizers. The dominant earthworm species were Eisenia fetida (Savigny, 1826), Dendrobaena veneta (Rosa, 1886), Dendrobaena hortensis (Michaelsen, 1890), Lumbricus terrestris (Linnaeus, 1758) and Aporrectodea longa (Ude, 1885). Seven different types of fertilizers including Urea, Ammonium sulfate (AS), Diammonium phosphate (DAP), Solupotas, NPK (15-5-25), (NPK+OM) and organic manure (OM) as experimental treatments were studied. Fluctuations in earthworm numbers and biomass were attributed to changes in time and depth of sampling, in addition to the types of fertilizers. The results of the means comparison showed that on the 20th day, at 0-20 cm soil depth, E. fetida species abundance was decreased significantly in AS and Urea treatments compared to the control plot (p˂0.05). We highlighted that from epigeic group, D. hortensis species had a better chance to survive and its population in AS treatment was more than that of Urea treatment. Results also showed that the anecic L. terrestris, had a greater tolerance to chemical fertilizers compared to the A. Longa species. The results of this study outline more clear horizons in managing the use of chemical fertilizers while simultaneously maintaining the biodiversity of soil organisms.